2021
DOI: 10.1155/2021/5594738
|View full text |Cite
|
Sign up to set email alerts
|

Deviation of Pedestrian Path due to the Presence of Building Entrances

Abstract: Commercial areas, especially urban ones with numerous buildings, are becoming increasingly prone to congestion because of their popularity. Visual inspections show that interactions between pedestrians and building entrances affect the distribution of pedestrian trajectories, which influences the utility of pedestrian spaces and the design of urban shopping areas. Herein, we analyse the dynamics of pedestrian deviations around building entrances. We used a video recorded using an unmanned aerial vehicle to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Several recent video-based experiments have looked into the motion of individuals and crowds within outdoor events (Helbing & Mukerji, 2012 ; Johansson et al, 2008 ), and these would seem to resonate with adjacent characteristics of retail high streets during mass events such as celebrations and festivals (Batty et al, 2003a , b ). Recent work by Sun et al ( 2021 ) has shown how commercially-available drone platforms can be used to analyze high street movement, in their case to examine the impact of building entrance geometry on the movement patterns of people on the street outside. Methods for machine learning from video could be useful in supporting knowledge-building of urban journeys in two key ways: (1) automated extraction of journey data from video footage of real streetscape scenes, and (2) the performance of streetscape audits to classify and label urban environment scenes in video.…”
Section: Existing Data Correspondences Between Retail Customer Journe...mentioning
confidence: 99%
“…Several recent video-based experiments have looked into the motion of individuals and crowds within outdoor events (Helbing & Mukerji, 2012 ; Johansson et al, 2008 ), and these would seem to resonate with adjacent characteristics of retail high streets during mass events such as celebrations and festivals (Batty et al, 2003a , b ). Recent work by Sun et al ( 2021 ) has shown how commercially-available drone platforms can be used to analyze high street movement, in their case to examine the impact of building entrance geometry on the movement patterns of people on the street outside. Methods for machine learning from video could be useful in supporting knowledge-building of urban journeys in two key ways: (1) automated extraction of journey data from video footage of real streetscape scenes, and (2) the performance of streetscape audits to classify and label urban environment scenes in video.…”
Section: Existing Data Correspondences Between Retail Customer Journe...mentioning
confidence: 99%
“…To apply the knowledge-driven approach in the pedestrian–object relation framework, a specialized hand-crafted model is required for every relation type. Yue et al, Li et al, and Sun et al [ 25 , 26 , 27 ] have illustrated the effort required to develop such a model.…”
Section: Introductionmentioning
confidence: 99%